1997
DOI: 10.2307/3870509
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Control of Phytochrome A Signaling in Arabidopsis

Abstract: The expression of the Arabidopsis plastocyanin (PC) gene is developmentally controlled and regulated by light. During seedling development, PC gene expression is transiently induced, and this induction can be repressed by sucrose. In transgenic seedlings carrying a PC promoter-luciferase fusion gene, the luciferase-induced in vivo luminescence was similarly repressed by sucrose. From a mutagenized population of such transgenic seedlings, we selected for mutant seedlings that displayed a high luminescence leve1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 30 publications
4
98
0
1
Order By: Relevance
“…This is similar to the position described for the sucrose-uncoupled6 (sun6, Dijkwel et al, 1997) mutant that was recently reported to encode ABI4 , an Apetala2-type transcription factor originally isolated as the abscisic acidinsensitive mutant abi4 (Finkelstein et al, 1998). Alleles of abi4 have also been identi®ed in sugar-sensing screens selecting for vegetative development on high-sugar media (Arenas-Huertero et al, 2000;Laby et al, 2000).…”
Section: Isolation Of Impaired Sucrose-induction Mutantssupporting
confidence: 79%
“…This is similar to the position described for the sucrose-uncoupled6 (sun6, Dijkwel et al, 1997) mutant that was recently reported to encode ABI4 , an Apetala2-type transcription factor originally isolated as the abscisic acidinsensitive mutant abi4 (Finkelstein et al, 1998). Alleles of abi4 have also been identi®ed in sugar-sensing screens selecting for vegetative development on high-sugar media (Arenas-Huertero et al, 2000;Laby et al, 2000).…”
Section: Isolation Of Impaired Sucrose-induction Mutantssupporting
confidence: 79%
“…Mutants which showed no repression of PC promoter activity by sucrose at the seedling stage were isolated (Dijkwel et aL, 1997). Three of them, sun I-2, sun6 and sun7, were backcrossed twice to the PC-LUC plants and retained their phenotype, sunl-2 and sun7 displayed a higher luciferase activity than the wild-type PC-LUC seedlings whereas sun6 plants had luminescence levels comparable to those of the PC-LUC plants (Dijkwel etal., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 17 such mutant lines were obtained and three of these were selected for detailed analysis. Genetic analysis shows that these sun1, sun6, sun7 mutations represent recessive Mendelian loci (Dijkwel et aL, 1997). In these mutants, the endogenous PC, CAB and RBCS steady-state mRNA levels were also sucrose-uncoupled at the seedling stage.…”
Section: Selection Of Arabidopsis Sucrose-uncoupled Mutantsmentioning
confidence: 99%
“…Recent studies have suggested that hexokinase, which was postulated to play an important role in sugar sensing in yeast (Ma et al, 1989;Rose et al, 1991), could be responsible for sensing sugars to repress a number of plant genes (Graham et al, 1994;Jang and Sheen, 1994). However, there are some examples of hexoseindependent changes in gene expression (Wenzler et al, 1989;Dijkwel et al, 1997) and in proton-Suc symporter activity (Chiou and Bush, 1998). Thus, mechanisms by which sugar is sensed and sugar signals are transduced are not completely clear yet.…”
mentioning
confidence: 99%